Perceptions of Divorce, Closeness, Marital Attitudes, Romantic Beliefs, and Religiosity Among Emergent Adults From Divorced and Nondivorced Families. Issue 3 (3rd April 2018) - Shimkowski, Jenna R.; Punyanunt-Carter, Narissra; Colwell, Malinda J.; Norman, Mary S.
ABSTRACT: This article analyzes 401 college students' perceptions of love, romance, parent–child closeness, and religiosity. Results revealed that college students from divorced homes were not as close with their parents and reported decreased religiosity compared to participants from nondivorced homes, and that these factors are associated with young adults' views and expectations on romantic relationships. The work presented here provides implications for future studies in understanding the beliefs about and effects of divorce for adult children. Further, results from this study suggest that college students have different expectations regarding love, romance, and marriage based on a number of family relation factors. Implications and suggestions for future research are discussed.